SYVN1, an ERAD E3 ubiquitin ligase, is involved in GABAAα1 degradation associated with methamphetamine-induced conditioned place preference - Jiao, Dong L.; Chen, Yan; Liu, Yao; Ju, Yun Y.; Long, Jian D.; Du, Jiang; Yu, Chang X.; Wang, Yu J.; Zhao, Min; Liu, Jing G. (Frontiers in Molecular Neuroscience, 2017)
Abuse of methamphetamine (METH), a powerful addictive amphetamine-type stimulants (ATS), is becoming a global public health problem. The GABAergic system plays a critical role in METH use disorders. By using rat METH conditioned place preference (CPP) model, we previously demonstrated that METH-associated rewarding memory formation was associated with the reduction of GABAAα1 expression in the dorsal straitum (Dstr), however, the underlying mechanism was unclear. In the present study, we found that METH-induced CPP formation was accompanied by a significant increase in the expression of Synovial apoptosis inhibitor 1 (SYVN1), an endoplasmic reticulum (ER)-associated degradation (ERAD) E3 ubiquitin ligase, in the Dstr. The siRNA knockdown of SYVN1 significantly increased GABAAα1 protein levels in both primary cultured neurons and rodent Dstr. Inhibition of proteasomal activity by MG132 and Lactacystin significantly increased GABAAα1 protein levels. We further found that SYVN1 knockdown increased GABAA α1 in the intra-ER, but not in the extra-ER. Accordingly, endoplasmic reticulum stress (ERS)-associated GRP78 and CHOP increased. Thus, this study revealed that SYVN1, as the ERAD E3 ubiquitin ligase, was associated with Dstr GABAAα1 degradation induced by METH conditioned pairing.